ANALISIS YURIDIS TERHADAP PERLINDUNGAN KONSUMEN DAN DAMPAKNYA PADA PRAKTIK BISNIS DI INDONESIA - Laura Sally Patricia; Ariawan (CV Rewang Rencang, 2024)
The implementation of consumer protection regulations in Indonesia plays a crucial role in shaping the relationship between businesses and consumers. This dynamic reflects how current policies strive to create a balance of interests, yet challenges remain in their execution. The existing regulations’ inability to fully protect consumers from harmful business practices raises questions about their effectiveness. Therefore, steps are needed to strengthen the consumer protection system, including stricter law enforcement and increased awareness among business actors, to foster fair and sustainable business practices.